Women's Leadership and the Law of Choosing Women Leaders in the Perspective of Islamic Law and Positive Law - Gunawan Abdi (ISNU Nine-Star Multidisciplinary Journal, 2024)
Women's leadership is an issue that continues to be debated in various societies, especially when associated with the perspective of Islamic law and positive law. In Islam, differences of opinion regarding women's leadership are often based on interpretations of verses of the Qur'an and hadith. One of the hadiths that is often used as a reference is "A people who entrust their affairs to a woman will not be fortunate" (HR. Bukhari). However, some scholars interpret this hadith contextually by considering the development of the times. Meanwhile, positive law in Indonesia guarantees equal rights for women to occupy leadership positions, as regulated in various laws and regulations. This study aims to analyze the legal legitimacy in choosing female leaders from the perspective of Islamic law and positive law. The method used is normative juridical with a conceptual and legislative approach through literature studies. The results of the study show that there are differences in interpretation in Islamic law regarding women's leadership, while positive law provides full guarantees for women's rights in leadership. In conclusion, women's leadership needs to be understood fairly by considering the principles of justice and gender equality in Islam and applicable legal regulations, in order to create a more inclusive and democratic leadership system.